THE ROLE OF LINGUISTICS IN ENGLISH LANGUAGE INSTRUCTION (American Journal of Pedagogical and Educational Research, 2023)
The purpose of this piece of research is to investigate the role of linguistics in ESL classrooms. Linguistics will be highlighted as an integral part of the English language classroom. Library research often called a literature review is the methodology employed. It employs both descriptive and comparative methods of data collection. This finding suggests that linguistics recognizes its educational role. There is a strong connection between linguistics and language education. This is due to the correlation between language instruction and linguistic development. How can a language instructor train students in writing without a firm grasp of the fundamentals of language study (spelling, morphology, syntax, semantics, and lexicology)? As a language instructor, he needs to be fluent in the target language and have a firm grasp of its rules to convey those laws to his students effectively.